Luther and the Ascetic Life - Yule, George (Studies in church history, 1985)
Luther’s attack on Medieval ascetic practices in general and on monasticism in particular was not because of asceticism as such, nor even because of the abuses that had come into monastic life, but because much of the theology that lay behind them undercut the evangelical understanding of salvation.This is the chief abomination of monasticism: we had to deny the grace of God and put our trust and hope in our holy monkery and not in the pure mercy and grace of Christ, as we had promised and begun to do in Christian baptism. For relying on works in order thereby to be justified and sanctified is in reality denying God’s grace, as St Paul clearly says (Gal. 5: 4:) ‘Christ is become of no effect unto you, whosoever of you are justified by the works of the law are fallen from grace’.